Digital terrain analysis in soil science and geology - Florinsky, Igor V (Oxford ; Waltham, MA : Academic Press, 2012)
"This book is the first attempt to synthesize knowledge on theory, methods, and applications of digital terrain analysis in the context of multiscale problems of soil science and geology. The content of the book is based on long-standing, interdisciplinary research of the author. The book is addressed to geomorphometrists, soil scientists, geologists, geoscientists, geomorphologists, geographers, and GIS scientists (at scholar, lecturer, and postgraduate student levels, with mathematical skills). This book is also intended for the GIS professionals in industry and research laboratories focusing on geoscientific and soil research. The book is divided into three parts. Part I represents main concepts, principles, and methods of digital terrain modeling. Part II discusses various aspects of the use of digital terrain analysis in soil science. Part III looks at applications of digital terrain modeling in geology"--
1Digital terrain modeling: a brief historical overview Part I: Principles and Methods of Digital Terrain Modeling 2 Morphometric variables 3 Digital elevation models 4 Calculation methods 5 Errors and accuracy 6 Filtering 7 Mapping and visualization Part II: Digital Terrain Modeling in Soil Science 8 Influence of topography on soil properties 9 Adequate resolution of models 10 Predictive soil mapping 11 Analyzing relationships in the system ''topography-soil'' Part III: Digital Terrain Modeling in Geology 12 Folds and folding 13 Lineaments and faults 14 Accumulation zones and fault intersections 15 Global topography and tectonic structures 16 Synthesis Appendix A: The mathematical basis of local morphometric variables by Shary, P.A. Appendix B: LandLord-- a brief description of the software
Includes bibliographical references and index
Keywords: Geology -- Data processing; Soils -- Analysis -- Data processing; Digital mapping